'Frozen' media subsidies during a time of media change: A comparative analysis of media policy drift in six Western democracies. (August 2014) - Nielsen, Rasmus Kleis
Media systems around the world have changed in significant ways in the early 21st century. In this article, I analyse how various forms of media subsidies have changed in response to these transformations in a sample of six different affluent democracies. On the basis of interviews, official documents and secondary sources, I show that media subsidies have largely remained frozen in their late-20th century form. The absence of major reform means that media subsidies are increasingly subject to policy drift, a process by which the operations and effectiveness of policies change not because of deliberate reform, but because of changing conditions on the ground. Analysis of interviews with relevant stakeholders suggests that the main obstacles to reform across all six countries are: (1) limited political attention to the problem; (2) strong incumbent industries protecting their interests; and (3) a perceived shortage of desirable, cost-effective, and governable alternatives to existing policies.